P49 Otosyphilis: missed opportunities for early treatment?. (23rd May 2012) - Bradshaw, D; Pallawela, S; Scott, C; Asboe, D; Nelson, M; Day, S
Abstract : Background: Otosyphilis (OS) is one of the few reversible causes of hearing loss. Audiological symptoms and positive syphilis (SP) serology can be diagnostic of OS. Hearing outcome after treatment is poor and evidence for optimal management is lacking. Aim: To identify how OS is managed in our unit. Method: Case collection and notes review. Results: Seven (6 male, 1 female) patients (pts) with OS were identified between 2007 and 2011, of median age 34 yrs. Of these 7 pts: 6 (86%) had secondary stage and 1 (14%) late stage SP; 6 (86%) were coinfected with HIV (2 testing HIV+ at SP diagnosis); all presented with deafness (bilaterally in 3 pts); all had other symptoms of SP (commonly rash (4, 57%) and ocular involvement (3, 43%)). Of 6/7 pts consenting to lumbar puncture, neurosyphilis was probable in 1 (17%), excluded in 2 (33%) and considered possible in 3 (50%) pts. Median time from audiological symptoms to treatment was 2 months (range 2 days to 6 m). Four (57%) had previously visited a health care professional who failed to diagnose OS. Six (86%) and 5 (71%) pts received a neurological regimen and steroid cover respectively. Overall, hearing improved in 3 (43%) and stabilised in 4 (57%) pts. An improved audiological outcome was seen in 2/3 (67%) pts receiving early treatment (within 1-month of hearing loss) vs 1/4 (25%) of those receiving late treatment and in 3/6 (50%) pts receiving a neurological regimen vs 0/1 pts receiving standard treatment. Median time to treatment was shorter in pts with established HIV infection (2 months) than those testing HIV+ at SP diagnosis or testing HIV neg (3.5 months). Conclusion: This small study identifies a delay to treatment in many cases. Early treatment and treating with a neurological regimen may improve outcome. HIV+ pts may have more regular SP testing, reducing the delay to treatment. OS is uncommon, but with increasing rates of SP nationally, we must be alert to its manifestations and promptly initiate treatment.